Phenotypic and Genomic Properties of Brachybacterium vulturis sp. nov. and Brachybacterium avium sp. nov. - Tak, Euon J.; Kim, Pil S.; Hyun, Dong-Wook; Kim, Hyun S.; Lee, June-Young; Kang, Woorim; Sung, Hojun; Shin, Na-Ri; Kim, Min-Soo; Whon, Tae W.; Bae, Jin-Woo (Frontiers in Microbiology, 2018)
Two strains VM2412T and VR2415T were newly isolated from the feces of an Andean condor (Vultur gryphus) living in Seoul Grand Park, Gyeonggi-do, South Korea. Cells of both strains were Gram-stain-positive, non-motile, aerobic, catalase-positive and oxidase-negative. Growth occurred at 10‒30°C, showing optimum growth at 30°C. They could stand up to 15% (w/v) NaCl concentration and grow at pH 6‒9. The strains shared 99.3% 16S rRNA gene sequence similarity each other but were identified as two distinct species based on 89.0‒89.2% ANIb, 90.3% ANIm, 89.7% OrthoANI and 38.0% dDDH values calculated using whole genome sequences. Among species with validly published names, Brachybacterium ginsengisoli DCY80T shared the highest 16S rRNA gene sequence similarities with strains VM2412T (98.7%) and VR2415T (98.4%) and the closest genetic relatedness with strains VM2412T (83.3‒83.5% ANIb, 87.0% ANIm, 84.3% OrthoANI and 27.8% dDDH) and VR2415T (82.8‒83.2% ANIb, 86.7% ANIm, 83.9% OrthoANI and 27.2% dDDH). Major fatty acid of the two strains was anteiso-C15 : 0 and polar lipids consisted of phosphatidylglycerol, diphosphatidylglycerol, phosphatidylethanolamine and three unidentified glycolipids. Strain VR2415T also had an unidentified phospholipid. Cell wall of the two strains contained meso-diaminopimelic acid as a diagnostic diamino acid and whole-cell sugars were ribose, glucose and galactose. They had MK-7 as a predominant menaquinone. Whole genomes of strains VM2412T, VR2415T and B. ginsengisoli DCY80T were newly sequenced in this study. The genomic G+C contents of strains VM2412T and VR2415T were 70.8 and 70.4 mol%, respectively. Genome-based phylogenetic tree constructed using an up-to-date bacterial core gene set (UBCG) showed that members of the genus Brachybacterium formed a clade with the isolated strains, supporting their taxonomic classification into the Brachybacterium spp. Based on phenotypic and genotypic analyses in this study, strains VM2412T and VR2415T are considered to represent two novel species of the genus Brachybacterium and the names Brachybacterium vulturis sp. nov. and Brachybacterium avium sp. nov. are proposed for strains VM2412T and VR2415T, respectively. Type strains are VM2412T (=KCTC 39996T=JCM 32142T) and VR2415T (=KCTC 39997T=JCM 32143T), respectively.